The impact of childhood injury and injury severity on school performance and high school completion in Australia: a matched population-based retrospective cohort study - Rebecca J. Mitchell; Cate M. Cameron; Anne McMaugh; Reidar P. Lystad; Tim Badgery-Parker; Tayhla Ryder (BMC, 2021)
Abstract Background Exploring the impact of injury and injury severity on academic outcomes could assist to identify characteristics of young people likely to require learning support services. This study aims to compare scholastic performance and high school completion of young people hospitalised for an injury compared to young people not hospitalised for an injury by injury severity; and to examine factors influencing scholastic performance and school completion. Method A population-based matched case-comparison cohort study of young people aged ≤18 years hospitalised for an injury during 2005-2018 in New South Wales, Australia using linked birth, health, education and mortality records. The comparison cohort was matched on age, gender and residential postcode. Generalised linear mixed modelling examined risk of performance below the national minimum standard (NMS) on the National Assessment Plan for Literacy and Numeracy (NAPLAN) and generalised linear regression examined risk of not completing high school for injured young people compared to matched peers. Results Injured young people had a higher risk of not achieving the NMS compared to their matched peers for numeracy (ARR: 1.12; 95%CI 1.06-1.17), reading (ARR: 1.09; 95%CI 1.04-1.13), spelling (ARR: 1.13; 95%CI 1.09-1.18), grammar (ARR: 1.11; 95%CI 1.06-1.15), and writing (ARR: 1.07; 95%CI 1.04-1.11). As injury severity increased from minor to serious, the risk of not achieving the NMS generally increased for injured young people compared to matched peers. Injured young people had almost twice the risk of not completing high school at year 10 (ARR: 2.17; 95%CI 1.73-2.72), year 11 (ARR: 1.95; 95%CI 1.78-2.14) or year 12 (ARR: 1.93; 95%CI 1.78-2.08) compared to matched peers. Conclusions The identification of characteristics of young people most likely to encounter problems in the academic environment after sustaining an injury is important to facilitate the potential need for learning support. Assessing learning needs and monitoring return-to-school progress post-injury may aid identification of any ongoing learning support requirements.